A Chiral Dual‐Core Organoboron Structure Realizes Dual‐Channel Enhanced Ultrapure Blue Emission and Highly Efficient Circularly Polarized Electroluminescence. Issue 36 (7th August 2022) - Yan, Zhi‐Ping; Yuan, Li; Zhang, Yuan; Mao, Meng‐Xi; Liao, Xiang‐Ji; Ni, Hua‐Xiu; Wang, Zhi‐Heng; An, Zhongfu; Zheng, You‐Xuan; Zuo, Jing‐Lin
Abstract: The realization of luminescent materials with narrowband and circularly polarized luminescence (CPL) is of great significance for the development of future optical and photonic devices. Herein, through a steric‐hindrance‐assisted dual‐core strategy, two pairs of chiral dual‐core multiple resonance thermally activated delayed fluorescence (MR‐TADF) materials ( R / S ‐DOBN and R / S ‐DOBNT) are directly constructed by the bonding of two organoboron MR‐TADF monocores (SOBN and SOBNT) with carbazole/3, 6‐di‐ tert ‐butyl‐9 H ‐carbazole and phenol derivative as donors, realizing obvious CPL and narrowband emissions. Furthermore, the dual‐core effect in the prepared R / S ‐DOBN and R / S ‐DOBNT increases the transition oscillator strength two times more than that of a monocore structure, while maintaining the ultrapure blue emissions peaking at 453 and 459 nm with a narrower full‐width at half‐maximum of 21 nm through reorganization energy reduction. The circularly polarized organic light‐emitting diodes based on the enantiomers exhibit ultrapure blue emission with Commission Internationale de L'Eclairage (CIE) coordinates of (0.14, 0.10) and (0.13, 0.12), high maximum external quantum efficiencies of 23.9% and 25.6%, and obvious circularly polarized electroluminescence with dissymmetry factors (| g EL |) ≈ 10 −3 . Abstract : Through a steric‐hindrance‐assisted dual‐core strategy, chiral organoboron structures are prepared by direct bonding of two multiple‐resonance thermally activated delayed fluorescence (MR‐TADF) monocores, realizing superior chiroptical property and dual‐channel enhanced ultrapure blue emission. Furthermore, highly efficient circularly polarized organic light‐emitting diodes (CP‐OLEDs) with maximum external quantum efficiencies of 23.9% and 25.6% are achieved.